2020
DOI: 10.1063/5.0029516
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-thin Hf0.5Zr0.5O2 thin-film-based ferroelectric tunnel junction via stress induced crystallization

Abstract: We report on 4.5-nm-thick Hf0.5Zr0.5O2 (HZO) thin-film-based ferroelectric tunnel junctions (FTJs) with a tungsten (W) bottom electrode. The HZO on the W electrode exhibits stable ferroelectricity with a remanent polarization of 14 μC/cm2, an enhanced tunneling electroresistance of 16, and excellent synaptic properties. We found that a large tensile stress was induced on a HZO thin film, owing to a low thermal expansion coefficient of the W bottom electrode. The low thermal expansion coefficient results in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 41 publications
5
80
0
1
Order By: Relevance
“…Numerous studies conducted in several research groups in the last decade have demonstrated that fluorite‐structure ferroelectrics can be deposited using various deposition techniques such as ALD, sputtering, pulsed laser deposition (PLD), chemical vapor deposition (CVD), and chemical solution deposition (CSD). [ 1–19,22–54 ] Among these techniques, ALD was the most intensively studied deposition technique because it can form very thin conformal and uniform ferroelectric films based on a self‐limiting mechanism by chemical reactions between metal precursors, oxygen source, and the previously deposited film (or substrate). In this regard, the only controllable parameters during the ALD process are types of metal precursor/oxygen sources, [ 27–29 ] pulse/purge time, [ 30,31 ] and deposition temperature.…”
Section: Deposition Methods For Low‐thermal‐budget Ferroelectric Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies conducted in several research groups in the last decade have demonstrated that fluorite‐structure ferroelectrics can be deposited using various deposition techniques such as ALD, sputtering, pulsed laser deposition (PLD), chemical vapor deposition (CVD), and chemical solution deposition (CSD). [ 1–19,22–54 ] Among these techniques, ALD was the most intensively studied deposition technique because it can form very thin conformal and uniform ferroelectric films based on a self‐limiting mechanism by chemical reactions between metal precursors, oxygen source, and the previously deposited film (or substrate). In this regard, the only controllable parameters during the ALD process are types of metal precursor/oxygen sources, [ 27–29 ] pulse/purge time, [ 30,31 ] and deposition temperature.…”
Section: Deposition Methods For Low‐thermal‐budget Ferroelectric Filmsmentioning
confidence: 99%
“…Depending on the type of material, the formation of the ferroelectric phase during the annealing process (or partially during the ALD process) can be enhanced by controlling the applied stress due to the difference in the thermal expansion coefficient or increasing the concentration of oxygen vacancies at the interface by the oxygenscavenging effect. [2,4,5,[47][48][49][50][51][52] In this regard, the influence of various bottom electrodes on ferroelectric properties has been extensively studied based on the metal-ferroelectric-metal (MFM) structure. [47][48][49][50][51] According to the experimental results reported in the past decade, the use of TiN bottom electrodes could be a useful strategy to improve the ferroelectric properties of Hf 1-x B x O 2 films.…”
Section: Substrate Materials For Low-thermal-budget Ferroelectric Fil...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the ferroelectricity and antiferroelectricity of doped HfO 2 -based fluoritestructured ferroelectric thin films have been extensively investigated since its first report by Böcske et al [1] In particular, various dopants, such as Si, Gd, Al, Y, La, Sr, and Zr have been reported [1][2][3][4][5][6][7][8] to stabilize the metastable (nonequilibrium) noncentrosymmetric orthorhombic (o) phase (space group Pca2 1 ) that is believed to be the origin of ferroelectric property. Among them, promising ferroelectric properties were observed at the near Hf x Zr 1Àx O 2 (x ¼ 0.5) composition ratio in most of the contributions, [7][8][9][10][11][12][13][14] therefore, the Hf 0.5 Zr 0.5 O 2 films with various dopants were investigated. [15,16] Müller et al first reported the observation of ferroelectricity in atomic layer deposited Hf 0.5 Zr 0.5 O 2 , [14] and then, the ferroelectric phase transition according to composition, covering the variable mixing range of Hf x Zr 1Àx O 2 films was also studied by sputtering [12,17] and ALD methods.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most addressed technique that have been reported in HfO 2 -based ferroelectric thin-film formation, is ALD, [1][2][3][4][5][6][8][9][10][11][12][13][14][15] because ALD of HfO 2 and ZrO 2 is already matured in the semiconductor industry. Particularly, ALD is thought to be one of the most practical deposition methods for 3D structure with a feature size approaching 10 nm or less due to an excellent thickness controllability, uniformity, and conformality for high aspect ratio structures.…”
Section: Introductionmentioning
confidence: 99%